Optimizing the collection of zakat Infak and Shadaqah using digital fundraising - Jumaati, Jumaati; Dahruji, Dahruji (Gema Wiralodra, 2024)
Yatim Mandiri is a national amil zakat institution that already has legitimacy through formal legal aspects in Surabaya and also has various kinds of programs to help orphans and the community. The purpose of this research of zakat infaq and shodaqah at laznas independent orphans in Surabaya. The method used in this study is a qualitative descriptive research method. For data collection techniques, researchers in this study, researchers used the theory of collecting zakat infak and shodaqah using digital fundraising. Development in zakat management is increasingly important along with the entry into the digital era.  used observation and interview techniques. Development in zakat management is felt to be increasingly important along with the entry in the digital era. Apart from that, it also concerns the form of digital fundraising strategies such as websites, email marketing, social media, search, in order to collect zakat more optimally. As a result, by transforming towards using channels in digital fundraising, management and collection programs, distribution and distribution of zakat infaq and shodaqah can be carried out better while the same time being able to educate the public about the obligation to tithe.